Leadership peace and cultural diplomacy in Nigeria (2015)
Many Classical authors such as Plutarch, Seutonius, Lucan, and even Julius Caesar himself have discussed Caesar’s conquests of his political opponents/enemies in the Roman senate and other lands. Modern authors such as Dodge, Goldsworthy, Gruen, and others have concentrated on Caesar’s personality, his victories and many others. Others have, in analysing this great leader, described him as a strategist, colossus, a military commander, gentle, assertive, cunning and authoritative, among many others. This paper aims to examine his strategy with regard to his securing his position as consul, his defeat of his political enemies in the Roman Senate, and other peoples. This paper argues that Julius Caesar’s philosophy of dealing devastating blows on his enemies, not only placed him on a pedestal of victory, it also placed Rome on a platform bereft of incursions from neighbouring peoples, especially the Gauls who were formidable enough to have sacked Rome in 390BC. The paper concludes with the argument that Julius Caesar would have died earlier than 44 BC if he had not adopted necessary measures to destroy his opponents, bringing honours upon himself and the Roman State.